Effectiveness of web application as educational media in increasing the caries risk knowledge and decreasing the caries risk score among dental students in Indonesia - Risqa Rina Darwita; Febriana Setiawati; Ishlah Fakhirah Rahmah (BMC, 2021)
Abstract Background This study evaluating the effect of web application media in increasing the caries risk knowledge and decreasing the caries risk scores among dental students. Methods A quasi-experimental design along with a purposive sampling technique was used in this study. A total of 361 undergraduate pre-clinical dental students from 15 universities in Indonesia were divided into two groups: intervention (n = 282) and control (n = 79). The students in the intervention group received a web application media with educational materials to independently check their caries risk, whereas those in the control group received the application without any educational materials. The students were instructed to use the web application at least once a week for 21 days and complete the pretest and posttest questionnaires and web application evaluation questionnaires. In addition, they were required to independently examine their initial and final caries risk. Results A significant increase in the level of knowledge was observed in the intervention group, but not in the control group, after the use of the web application. Each group showed a decrease in the caries risk score, but the difference was not statistically significant before and after the use of a web application in both groups. Conclusion These findings indicate that health promotion and education about caries risk through web application media can improve the knowledge and reduce the caries risk in dental dentistry students.